2004
DOI: 10.1101/gad.289504
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle-dependent dynamic localization of a bacterial response regulator with a novel di-guanylate cyclase output domain

Abstract: Pole development is coordinated with the Caulobacter crescentus cell cycle by two-component signaling proteins. We show that an unusual response regulator, PleD, is required for polar differentiation and is sequestered to the cell pole only when it is activated by phosphorylation. Dynamic localization of PleD to the cell pole provides a mechanism to temporally and spatially control the signaling output of PleD during development. Targeting of PleD to the cell pole is coupled to the activation of a C-terminal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
662
2
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 563 publications
(698 citation statements)
references
References 56 publications
(59 reference statements)
20
662
2
6
Order By: Relevance
“…Although the biological pathways through which c-di-GMP regulates persistence, cell aggregation and the switch to the commensal lifestyle are currently poorly understood, the proteins responsible for c-di-GMP synthesis and degradation have been determined and, at least partially, characterized. Bacterial diguanylate cyclase (DGC) activity is found in GGDEF domain-containing proteins (Paul et al, 2004;Ryjenkov et al, 2005;Hickman et al, 2005;Kulesekara et al, 2006), whilst EAL domain-containing proteins have been shown to have c-di-GMP-specific phosphodiesterase (PDE) activity (Bobrov et al, 2005;Christen et al, 2005;Schmidt et al, 2005;Kulesekara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the biological pathways through which c-di-GMP regulates persistence, cell aggregation and the switch to the commensal lifestyle are currently poorly understood, the proteins responsible for c-di-GMP synthesis and degradation have been determined and, at least partially, characterized. Bacterial diguanylate cyclase (DGC) activity is found in GGDEF domain-containing proteins (Paul et al, 2004;Ryjenkov et al, 2005;Hickman et al, 2005;Kulesekara et al, 2006), whilst EAL domain-containing proteins have been shown to have c-di-GMP-specific phosphodiesterase (PDE) activity (Bobrov et al, 2005;Christen et al, 2005;Schmidt et al, 2005;Kulesekara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the publication of much biological data concerning GGDEF domains, biochemical demonstration of DGC activity (Paul et al, 2004;Ryjenkov et al, 2005), and the solution of the crystal structure of the GGDEF response regulator PleD (Chan et al, 2004), detailed structurefunction analyses of GGDEF proteins are relatively scarce. Christen et al (2006) have analysed the site of c-di-GMP product inhibition (the 'I site') for the Caulobacter crescentus enzymes PleD and DgcA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two domains are thought to interact with cyclic-diguanosine monophosphate (c-di-GMP), and c-di-GMP was recently proposed to be a global secondary messenger involved in regulating cell-cell and cell-surface interactions (9). The GGDEF domain was recently shown to be associated with the synthesis of c-di-GMP via diguanylate cyclase (DGC) and the EAL domain to contain phosphodiesterase (PDE) activity in Yersinia, Caulobacter, and Salmonella (9,16,27,24,38) and more recently in Shewanella (54). In addition, the involvement of DGC and PDE domains in cell metabolism and cell behavior has recently been shown in Burkholderia, Xanthomonas, Streptococcus, Vibrio, and Pseudomonas (for examples, see references 5 and 30).…”
Section: Resultsmentioning
confidence: 99%
“…The SO3389 ORF also contains putative GGDEF and EAL domains (originally named for the conserved amino acid residues) (9,24,38). The two domains are thought to interact with cyclic-diguanosine monophosphate (c-di-GMP), and c-di-GMP was recently proposed to be a global secondary messenger involved in regulating cell-cell and cell-surface interactions (9).…”
Section: Resultsmentioning
confidence: 99%